Aplicación del papanicolaou para detección del virus del papiloma humano (VPH) en pacientes atendidas en el centro de salud del Cantón Caluma, noviembre 2023- abril 2024. - Guerrero Hidalgo, Marcia Piedad (2024)
The Papanicolaou test allows for the timely diagnosis of lesions caused by the human papillomavirus. Objective: Analyze the application of the Papanicolaou test to detect the human papillomavirus in patients treated at the Caluma Canton Health Center, November 2023-April 2024. Methodology: Observational, quantitative, applied, descriptive, field and transversal. Results: Regarding knowledge about the Pap test, it was evident that they had heard about the Pap test (63.1%), correct definition (52.3%) and frequency 2 or 3 years ago (29.2% ); Regarding knowledge about the human papillomavirus, they had never heard of it (67.7%), correct definition (11.5%) and identification of preventive measures (14.6%); factors associated with the development of human papillomavirus, age from 20 to 24 years and from 35 to 39 years (24.6%), secondary educational level (40.0%), urban-marginal origin (40.0%), housewives (49.2%), 2-3 sexual partners (37.7%) and never use a condom (53.8%). Conclusion: There is a lack of knowledge among women about the importance of the Pap test and the prevention of human papillomavirus.